Using the Ages & Stages Questionnaire to assess later effects of an infant intervention promoting language in primary care - Gretchen J. Domek; Lori Silveira; Helene Kuffel; Lauren Heller Szafran; Andrea Jimenez-Zambrano; Bonnie W. Camp (BMC, 2023)
Abstract Background Positive relational experiences during infancy have a profound impact on child development and are critical for future health and school readiness. We have been evaluating a simple finger puppet intervention that takes one minute and costs $1USD to deliver in the primary care setting to promote caregiver-infant interactions. We explored using developmental trajectories to determine later outcomes of our early intervention program by comparing trajectories to age 36 months to assess optimal intervention timing when delivered in early versus late infancy. Methods Three cohorts were enrolled and given a puppet at 2 months (early intervention) and 6 or 12 months (late intervention). Child development was assessed using the Ages & Stages Questionnaires (ASQ-3), which were independently collected during well visits. Scanned ASQ-3 forms from 2 to 36 months were obtained retrospectively through the electronic medical record. To compare longitudinal scores at different ages, all raw scores were first converted to z-scores. Longitudinal mixed effects models examined the trajectories of participant ASQ-3 scores over time by comparing the average intercepts and slopes. Results Of 180 children enrolled, 172 (96%) completed 2 or more ASQ-3 questionnaires and were included in the analysis, with a mean of 4.9 and a total of 843 questionnaires. Most children (85%) were on government-sponsored insurance. There were no statistical differences comparing cohort intercepts, while early intervention had a significant difference in slope compared to late intervention for the Personal-Social domain (0.12, p=0.018), resulting in higher predicted scores at 36 months. Early compared to late intervention had a difference in slope approaching significance for Communication (0.14, p=0.056) and the combined non-motor score (0.33, p=0.052). There were no significant differences in slope for Problem Solving (0.05, p=0.48), Gross Motor (-0.009, p=0.84), Fine Motor (0.06, p=0.22), and total ASQ-3 (0.32, p=0.17) scores. Conclusions Finger puppets may provide a simple and scalable way to encourage responsive caregiver-infant interactions promoting language and social-emotional development, especially when provided in early versus late infancy. Our trajectory analysis also demonstrates a useful and potentially cost-effective approach to evaluating long-term developmental outcomes of an early intervention.